Evaluating the impact of a nationally recognised training programme that aims to raise the awareness and challenge attitudes of personality disorder in multi-agency partners. Issue 2 (3rd June 2014) - Lamph, Gary; Latham, Cameron; Smith, Debra; Brown, Andrew; Doyle, Joanne; Sampson, Mark
Abstract : Purpose: – An innovative training initiative to raise the awareness of personality disorder and enable more effective working with people with personality disorder who come into contact with the wider multi-agency system has been developed. For the purpose of the training initiative the nationally recognised Knowledge and Understanding Framework (KUF, awareness-level programme) has been employed. An overview of the comprehensive multi-agency training initiative will be outlined with reporting and discussion of the outcome data provided within this paper. The paper aims to discuss these issues. Design/methodology/approach: – This paper outlines the development and outcomes of a service evaluation study. The utilised outcome measures were carried out at pre-, post- and three-month follow-up measures. The Personality Disorder-Knowledge Attitude and Skills Questionnaire was utilised on the recommendation of the central team. Additionally a Visual Analogue Scale was developed for the purpose of this study was also employed. Findings: – Data findings are positive particularly when comparing pre- and post-results and the pre- and follow-up results. There appears to be an apparent peak in results post-training which could be attributed to the fact that knowledge and understanding is recent and fresh in the delegates mind, however positive results are still reported at follow-up there does appear to be decline in results and durability of the effect when three-month follow-up is compared against the post-training results. Research limitations/implications: – Follow-up was at three months, which is a relatively short-time span post-training it would be of great interest to see in the future if the decline in the three areas continues. If this was followed up and if this pattern continued this could provide us with evidence to support the development of refresher courses. In the future, due to the multi-agency design of this service evaluation, comparisons of the different sectors, agencies and occupations involved, could also be explored further to establish what multi-agency areas the training has had the most effect and impact. Practical implications: – High levels of demand from multi-agencies to receive training in personality disorder is reported. Our findings and experience provide evidence that multi-agencies partners from a variety of professional backgrounds can effectively work in partnership with people with lived experience to effectively deliver the KUF training. Social implications: – This innovative roll-out of KUF training provides evidence that with a little investment, a comprehensive multi-agency roll-out of KUF is achievable and can provide statistically significant positive results displaying the effectiveness and change brought about via the KUF training. Originality/value: – The originality of this sustainable and low-cost approach to educating the wider system is reported in this paper. This has lead to the strategy receiving national recognition winning a nursing times award in 2011 and a model of innovative practice nationally.